GREEN SOVEREIGN BONDS: A FINANCIAL OPPORTUNITY OR RISK FOR DEVELOPING COUNTRIES? - Jumaniyazov I. T; Aminova N. U. (Modern American Journals, 2025)
This article investigates the emergence and growth of green sovereign bonds in developing countries as a tool for financing climate-related infrastructure and achieving sustainability goals. Using the IMRaD framework, the paper analyzes bond issuances from 2020 to 2024 in Uzbekistan, Chile, Indonesia, Kazakhstan, and Azerbaijan. Based on quantitative data from the World Bank, IMF, Climate Bonds Initiative, and official national sources, we compare the structure, terms, yields, and proceeds of green bonds across these countries. The findings reveal that while green sovereign bonds offer substantial opportunities to access ESG capital and finance environmental goals, they also carry risks such as greenwashing, high debt servicing costs, and currency mismatches. Uzbekistan and Indonesia illustrate how carefully structured green bonds can mobilize climate finance effectively, while Chile demonstrates large-scale success in deploying international capital for green infrastructure. The paper concludes with policy recommendations to improve governance, transparency, and fiscal integration of green bond strategies in emerging markets.
Keywords: Green sovereign bonds; Climate finance; Developing countries; Uzbekistan; Indonesia; Chile; ESG investment; Greenwashing; Public debt; SDG bonds; Sustainability-linked finance; IMF; Climate Bonds Initiative